National and subnational burden of brain and central nervous system cancers in Iran, 1990–2019: Results from the global burden of disease study 2019 - Mahdi Mahdavi; Sahar Saeedi Moghaddam; Mohsen Abbasi-Kangevari; Esmaeil Mohammadi; Parnian Shobeiri; Guive Sharifi; Ali Jafari; Negar Rezaei; Narges Ebrahimi; Nazila Rezaei; Seyyed-Hadi Ghamari; Mohammad-Reza Malekpour; et al. (Cancer Medicine, 2023)
Central nervous system cancers (CNS cancers) impose a significant burden upon healthcare systems worldwide. Currently, the lack of a comprehensive study to assess various epidemiological indexes of CNS cancers on national and subnational scales in Iran can hamper healthcare planning and resource allocation in this regard. This study aims to fill this gap by providing estimates of CNS cancer epidemiological measures on national and subnational levels in Iran from 1990 to 2019. This study is a part of Global Burden of Disease (GBD) 2019 that contains epidemiological measures including prevalence, incidence, mortality, Disability-Adjusted Life Years (DALYs), Years Lived with Disability (YLDs), and Years of Life Lost (YLLs) of CNS cancers. Age standardization was utilized for comparing different provinces. In 2019, 5811 (95% Uncertainty Interval: 2942–7046) national new cases and 3494 (1751–4173) deaths due to CNS cancers were reported. National age-standardized incidence (ASIR), deaths (ASDR), and DALYs rates were 7.3 (3.7–8.8), 4.6 (2.3–5.5), and 156.4 (82.0–187.0) per 100,000 in 2019, respectively. Subnational results revealed that ASDR and ASIR have increased in the past 300.167emyears in all provinces. Although incidence rates have increased in all age groups and genders since 1990, death rates have remained the same for most age groups and genders except for young patients aged under 15, where a decrease in mortality and YLLs can be observed. The incidence, deaths, and DALYs of CNS cancers increased at national and subnational levels. These findings should be considered for planning and resource allocation.
Keywords: 330